JONATHAN EDWARDS AND FRANCIS TURRETIN ON NECESSITY, CONTINGENCY, AND FREEDOM OF WILL. IN RESPONSE TO PAUL HELM - Muller, Richard A. (Jonathan Edwards studies, 2014)
In his own time, as well as throughout the nineteenth century, Edwards’ views were both criticized and praised as a departure from Reformed understandings of free choice, defended as fully compatible with Reformed doctrine including the formulations found in the Westminster Standards albeit somewhat more deterministic than the older tradition, and applauded as finally moving Reformed thought on the subject into a philosophically adequate determinist framework. These debates took place both in Edwards’ own North American context and also in Great Britain and involved such thinkers as Joseph Priestley, Dugald Stuart, William Hamilton, William Cunningham, John Lafayette Girardeau, and Robert Dabney. My recent essay lining out the British debates and indicating Edwards’ departure from the patterns of thought found in the older Reformed orthodoxy has been challenged by Paul Helm, who argues that Edwards’ philosophical compatibilism can be readily assimilated to the teachings of the Reformed orthodox.